2017
DOI: 10.3831/kpi.2017.20.004
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract of Plumbago Zeylanica - A Remarkable Antibacterial Agent Against Many Human and Agricultural Pathogens

Abstract: Objectives:The current investigation was carried out to determine the cytotoxic and the antimicrobial activities of methanolic extracts of Plumbago zeylanica.Methods:The stems, leaves, and whole plants were air dried and extracted with methanol by using a Soxhlet extractor for 72 hours at 55 - 60°C. The antimicrobial activities were determined from the zones of inhibition, which were measured by using the agar well diffusion method, and the cytotoxicity assays were performed using the 3-(4,5-dimethylthiazol-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In the light of the increasing problem of antibiotic resistance, the antimicrobial properties of plant extracts may be of high value in clinical medicine. Some bioactive compounds have shown antifungal activity, which is also of interest in medicine, in pharmaceutics, and in plant sciences [ 11 ].…”
Section: Medicinal and Aromatic Plantsmentioning
confidence: 99%
“…In the light of the increasing problem of antibiotic resistance, the antimicrobial properties of plant extracts may be of high value in clinical medicine. Some bioactive compounds have shown antifungal activity, which is also of interest in medicine, in pharmaceutics, and in plant sciences [ 11 ].…”
Section: Medicinal and Aromatic Plantsmentioning
confidence: 99%
“…P. zeylanica is a pharmacologically important plant. It exhibits broad range of pharmacological activities, which include antibacterial, antifungal, anti-inflammatory, antioxidant, and wound healing (Shweta and Dubey, 2015;Singh et al, 2017;Aleem, 2020). G. superba shows oxytocic activity and acts as an early abortifacient, maintains labour, aids the timely removal of placenta, and minimizes post-partum bleeding.…”
Section: Discussionmentioning
confidence: 99%
“… Mehrbod et al (2018) ; Madikizela and McGaw (2019) Plumbaginaceae Plumago zeylanica L. Dyspnoea (shortness of breath) Anti-inflammatory, anti-malarial, antiviral, antifertility, antimicrobial, antioxidant, blood coagulation, wound healing, memory enhancer and anti-cancer activities. Toxic LD 50 – 65 mg/kg Parker et al (2007) ; Mandavkar and Jalalpure (2011) ; Ganesan and Gani (2013) ; Jain et al (2014) ; Sharma and Kaushik (2014) ; Singh et al (2017) ; Jain et al (2020) Poaceae Phragmites mauritianus Kunth Pneumonia no records found no records found Polygalaceae Securidaca longipedunculata Fresen. Tuberculosis and pneumonia Antiviral, antifungal, antimicrobial, antioxidant, anti-inflammatory and antibacterial activities.…”
Section: Methodsmentioning
confidence: 99%